Implikasi Hak Kebendaan terhadap Jaminan Fidusia dalam Kredit Perbankan (Studi Kasus PT. BANK SUMUT) - Muhammad Reza Pahlevi Nasution; Rostrianda Siallagan; Fera Angelina Ginting; Tanti Wijayanti Oktavia; Satria Braja Hariandja (Mahesa Research Center, 2020)
In a variety of credit systems offered by PT. Bank Sumut Branch Of Medan turned out to have various methods in its procedural. This journal aims to find out the conditions set by PT. Bank Sumut Branch Of Medan as a creditor to each debtor,the research method used is judiscial empiricial that is by conducting field research, the results of the study show the creditor has the same absolute conditions for each type and nature of the credit offered, in its determination the debtor must be able to provide a collateral object in the form of fiduciary the object is a ceiling of 125% of what the debtor gets and the executor of PT. Bank Sumut Branch Of Medan is still carried out according to warnings made by company through 3 phases of summons, then if the debtor does not have good faith in paying off his debts, the creditor can sue the debtor for trial and obtain a district court decision as the basis for executing the fiduciary guarantee object in material rights. With the result of the transfer of material rights, the existence of the object of fiduciary collateral is wholly owned by the creditor and can be auctioned off at the KPKNL and can also be through the absolute surrender of PT. Bank Sumut Branch Of Medan by selling it real execution.